2020
DOI: 10.1021/acs.inorgchem.0c00857
|View full text |Cite
|
Sign up to set email alerts
|

A Chemodosimetric Approach for Fluorimetric Detection of Hg2+ Ions by Trinuclear Zn(II)/Cd(II) Schiff Base Complex: First Case of Intermediate Trapping in a Chemodosimetric Approach

Abstract: The present work discloses the application of two fluorescent zinc and cadmium complexes (1 and 2) for sensing of Hg(II) ions through a chemodosimetric approach. The ligand under consideration in this work is a N 2 O donor Schiff base ligand (E)-4-bromo-2-(((2-morpholinoethyl)imino)methyl)phenol (HL), which has been harnessed to generate complexes [Zn 3 L 2 (OAc) 4 ] (1) and [Cd 3 L 2 (OAc) 4 ] (2). X-ray single crystal diffraction studies unveil the trinuclear skeleton of complexes 1 and 2. Both complexes hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 83 publications
0
12
0
Order By: Relevance
“…To understand in detail the electronic transition behavior of 1, 2 , and 4 , DFT calculations 24 for 1 were performed. DFT calculations show that the transition corresponding to 352.79 nm is for the H-2 → L/H-3 → L/H-4 → L/H-1 → L/H-6 → L molecular orbital (MO) transition of an oscillator strength ( f ) of 0.0116, which is close to the experimental value of 355 nm ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand in detail the electronic transition behavior of 1, 2 , and 4 , DFT calculations 24 for 1 were performed. DFT calculations show that the transition corresponding to 352.79 nm is for the H-2 → L/H-3 → L/H-4 → L/H-1 → L/H-6 → L molecular orbital (MO) transition of an oscillator strength ( f ) of 0.0116, which is close to the experimental value of 355 nm ( Table S5 ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the electrospun fibrous strips with grafted TPE and dithioacetal moieties are designed for the detection of trace Hg 2+ with the visual change of color strip from green to blue [107]. Abani et al [108] reported a trinuclear Zn(II)/Cd(II) Schiff base complexes 80 and 81 for the detection of Hg 2+ in aqueous medium via chemodosimetric approach (Figure 27). Two absorption maxima at 388 nm and 390 nm were red-shifted and the colorless solution turned to distinct yellow.…”
Section: Reaction-based Chemosensorsmentioning
confidence: 99%
“…Over the years, salen‐type N 2 O 2 ‐donor ligands, [ 1–5 ] as building units of polymetallic systems, have attracted more and more attention. [ 6–8 ] These N 2 O 2 ‐donor ligands can form a variety of complexes and exhibit unique optical [ 9–11 ] and catalysis properties [ 12,13 ] and are currently of interest because of their potential applications in the preparation of new optical or catalysis materials and perfect probes. [ 14,15 ] In addition, they have outstanding performance in supermolecular building and chiral complexes.…”
Section: Introductionmentioning
confidence: 99%